A Rosetta Stone for Breast Cancer: Prognostic Value and Dynamic Regulation of Neutrophil in Tumor Microenvironment - Zhang, Wei; Shen, Yimin; Huang, Huanhuan; Pan, Sheng; Jiang, Jingxin; Chen, Wuzhen; Zhang, Ting; Zhang, Chao; Ni, Chao (Frontiers in Immunology, 2020)
Increasing evidence has revealed that the initiation and progression of breast cancer are greatly affected by the immune environment. Neutrophils are the most abundant leucocytes in circulation and act as the spearhead in inflammation, including in breast cancer. Circulating neutrophils are closely related to the prognosis of breast cancer patients, and tumor-infiltrating neutrophils have varied functions at different stages of breast cancer, such as antitumor or tumor-promoting neutrophils, which are termed N1 and N2 neutrophils, respectively. In this review, we will discuss the utility of circulating neutrophils for predicting prognosis and therapeutic efficacy and the underlying mechanisms of their chemotaxis, the dynamic regulation of their antitumor or protumor functions and their different spatial distributions in tumor microenvironment. Finally, we also discuss the possibility of targeting neutrophils as a therapeutic strategy in breast cancer.